Open innovation governance modes: what mode Is right for you? - Bagherzadeh, Mehdi (Henry Stewart Talks, 2021)
Open Innovation, Open Innovation governance modes, Problem complexity and Open Innovation governance modes, Knowledge hiddenness and Open Innovation governance modes, Examples of Open Innovation